THE SIGNIFICANCE OF DIFFERENT METHODS FOR DETECTION OF GASTROESOPHAGEAL REFLUX IN CHILDREN - Ristić, Nina Z; Kisic Tepavcevic, Darija; Milovanović, Tamara (Medicinski podmladak, 2018)
Symptom-based diagnosis of gastroesophageal reflux disease (GERD) is not specific due to high prevalence of disorders that can mimic GERD. Conventional pH monitoring, combined pH-MII (multiple intraluminal impedance) monitoring and esophagogastroduodenoscopy are most frequently used diagnostic methods in children. Combined pH-MII monitoring is the most accurate diagnostic method for detecting GERD in children, which tends to become the gold standard. In infants and probably in children with extraesophageal symptoms MII gives the greatest contribution to the validity of pH-MII monitoring. High prevalence of functional heartburn in children older than 8 years suggests the importance of pH-MII monitoring in this age group as well. The majority of studies showed age differences in the chemical composition of refluxate. Weakly acid reflux is more common in infants and is often associated with symptoms, whereas acid reflux is more common in older children and adolescent. Sensitivity of endoscopy is very low compared to pH-MII monitoring as a reference test. Although endoscopy is the method of choice for the confirmation of reflux esophagitis, pH-MII parameters are promising indicators of mucosal integrity, but further studies are needed. The major problem with pH-MII monitoring is a lack of normative data for children, therefore standardization is mandatory. For the present pH-MII monitoring has limited impact on treatment due to the absence of effective therapy for weakly acid reflux, suggesting that further studies should be directed in this direction.